Two solvent-stable MOFs as a recyclable luminescent probe for detecting dichromate or chromate anions. Issue 23 (10th May 2016) - Cao, Chun-Shuai; Hu, Huan-Cheng; Xu, Hang; Qiao, Wan-Zhen; Zhao, Bin
Abstract : Two unique 2D Zn-MOFs with high thermo-stability, solvent-stability and pH-stability can efficiently and selectively detect Cr2 O7 2− /CrO4 2− among twenty-one anions. Importantly, they can be regenerated by a simple and rapid method in detecting Cr2 O7 2− /CrO4 2− . Abstract : Two unique 2D Zn-MOFs with the formulas {[Zn(btz)] n } (1 ) and {[Zn2 (ttz)H2 O] n } (2 ) were synthesized using in situ generated ligands under hydro(solvo)thermal conditions. Both1 and2 exhibit high thermo-stability, solvent-stability and pH-stability. Thermogravimetric analyses (TGA) reveal that1 and2 remain intact until about 365 °C and 332 °C, respectively. The samples of1 and2 were immersed in twelve common solvents for 24 hours, and the obtained PXRD patterns remain well consistent with the simulated ones. They were immersed in a series of solutions with pH values ranging from 1.0 to 14.0 for five hours, and the PXRD patterns of these samples remain unchanged spanning the pH range of 1–13. The luminescence investigations reveal that the compounds1 and2 can efficiently and selectively detect Cr2 O7 2− or CrO4 2− among twenty-one anions. Importantly, they can be regenerated by a fast and simple method in detecting Cr2 O7 2− or CrO4 2− .